Sparta and its citizens: between honor and shame - Carminati, Luis Henrique (Romanitas - Revista de Estudos Grecolatinos, 2023)
Book review of: BERNARDO, G. C. Comandantes e covardes: honra e mérito em Esparta. São Paulo: Intermeios, 2020. 410 p.
Keywords: Sparta; Honor; Merit; Shame